The Use of English Literacy in Improving the Development of Health Student Research - Nurrochim Nurrochim; Aris Widiyanto; Joko Atmojo; Asruria Sani Fajria (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Health literacy has received considerable attention in its development because of its important role in the world as a means to improve health and reduce health. The important role of literacy is needed for students as students at the highest level, where good literacy skills will determine academic achievement in lectures. The purpose of this study was to find out how literacy in English can improve the development of health student research. The design of this study used a cross sectional approach which was carried out at Stikes Mambaul Ulum Surakarta, Central Java. A sample of 120 people was taken using a stratified random sampling technique, then divided into two groups, each group collecting 60 people. Analysis of the data using independent t-test with the results obtained that of the two groups known to have the highest average developmental score found in the student group using English literacy research (Mean IP = 3.57). These results show that the differences in research development in the group of students not using English literacy and the group of students using English literacy were statistically significant (p < 0.001). It was also found that the group of students using English literacy increased student research development with an effect value (ES = 7.60) compared to the group of students who did not use English literacy.